Peningkatan Keterampilan Wudhu Melalui Metode Demonstrasi Pada Siswa Kelas I Di SD Negeri 1 Kutosari - Ika Rifa Rofifah; Lutthfiyatu Zahro; Siti Fatimah; Atim Rinawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the improvement of students' ablution skills through the demonstration method for class I B students in semester II at SD Negeri 1 Kutosari in the 2022/2023 academic year. This research was conducted using Classroom Action Research (CAR). PTK aims to improve the quality of learning through action on students. The research was conducted in two cycles, namely cycle I and cycle II. In each cycle there are stages of planning, implementing, observing, and reflecting. The research subjects were first grade students at SD Negeri 1 Kutosari. Data collection techniques carried out were tests, non-tests, observations, interviews, and documentation. Data validity was carried out using triangulation, namely source triangulation and technique triangulation. The results showed that in the first cycle of students who completed reached 45%, and in the second cycle the completeness of students reached 85%. So, it can be concluded that through Class Action Research there is an increase in students' ablution skills through the demonstration method.